1997
DOI: 10.2355/isijinternational.37.677
|View full text |Cite
|
Sign up to set email alerts
|

The .DELTA. to .GAMMA. Transition in Fe-Cr-Ni Alloys during Laser Treatment.

Abstract: Lausanne. Switzerland. Laser

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 0 publications
1
28
1
Order By: Relevance
“…Microstructural transition was evaluated by changing the composition over the length of the dissimilar alloy weld 17,19) as shown in Fig. 2.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microstructural transition was evaluated by changing the composition over the length of the dissimilar alloy weld 17,19) as shown in Fig. 2.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…15) Moreover, the microstructural transition between d and g during laser experiments has been evaluated. 17) It was shown that the transition from d to g was controlled by the dendrite growth kinetics (i.e., no nucleation barrier exists) and that this transition could be predicted by theory. To the contrary, the reverse transition from g to d was inferred to be controlled by the nucleation of ferrite at the growing g-dendrite front.…”
Section: Introductionmentioning
confidence: 99%
“…Fukumoto and Kurz extended the binary model for dendrite solidification to the multicomponent Fe-Cr-Ni-C system by coupling the calculations with computational thermodynamics. [52][53][54] We have adopted the same approach here and have applied it to the Fe-C-Al-Mn system. The results [see Fig.…”
mentioning
confidence: 99%
“…The Kurz -Giovanola -Trivedi (KGT) model is known to be applicable for such rapid solidification process as the transition of the primary phase on solidification might occur. Recently, the modified KGT model which is extended to alloys with multicomponents has been developed [7,8]. The modified KGT model was used for the analysis on the transition of solidification mode in the weld metal of stainless steels.…”
Section: Theoretical Model and Calculationsmentioning
confidence: 99%